Early-age and long-term strength development of high-performance concrete with SAP. (18th January 2021) - Olawuyi, Babatunde J.; Babafemi, Adewumi J.; Boshoff, William P.
Highlights: Early-age and long-term compressive strength of low W/B HPC with SAP as IC-agent was investigated. 70 MPa as minimum strength were studied with 25 g/g extra water provided for SAP absorption. Variables considered are SAP content, size, binder type, w/b ratio and curing age. Compressive strength of HPC slightly decreased with increase in SAP content. SAP's absorption into Power's Model shows compatibility for prediction of strength development. Abstract: Internal curing of high-performance concrete (HPC) by the addition of Superabsorbent Polymers (SAP) has been proven to be effective in mitigating autogenous shrinkage. The issues of concern in research, however, is the extent to which strength development is impacted by the voids created by SAP as cement hydrates with age. In this study, the influence of SAP content, size, binder type, water/binder ratio (W/B) and curing age on the early-age and long–term strength development of a low W/B HPC was examined. HPC mixtures designed for a minimum 28-day target cube strength of 70 MPa (i.e. C55/67 – C100/115) were studied with 25 g/g extra water provided for SAP absorption. Mortar (50 mm) and concrete (100 mm) cubes were cast and cured in water for different hydration periods. The results reveal that the compressive strength of the HPC mixtures decreased slightly (both for the early-age and long-term) as SAP content increased. Statistical examination of the results further revealed that W/B and SAP contents significantly influenced the strength development while a simulation of the SAP's water absorption into Powers' Model show compatibility for prediction of strength development trends in HPC with SAP.